Enhanced Recovery After Caesarean Delivery: A Narrative Review - intan Nurhayati; Mardiati Nadjib (Universitas Nahdlatul Ulama Surabaya, 2023)
Enhanced recovery after surgery (ERAS) is a philosophy of perioperative care that has been used in other fields since the 1990s but has only recently been applied to obstetric care in the form of Enhanced Recovery After Caesarean Delivery (ERACS). This review highlights perioperative care in ERACS, ERACS guidelines, and the benefits of ERACS. ERACS is a multimodal-based perioperative management protocol to recover the patient's condition immediately. It maintains preoperative organ function and reduces stress response during surgery. The primary keys in this protocol include preoperative counseling, optimization of nutrition, use of standard anesthetic and multimodal analgesia drugs, and early mobilization. The protocol covers perioperative care, from preoperative, intraoperative and postoperative. It involves a multidisciplinary team of anesthesiologists, surgeons, nurses, and nutritionists. The ERACS has many benefits, including shortening the duration of hospitalization, decreasing anxiety and stress, reducing the risk of postoperative infection, and accelerating the body's recovery. In addition, there are faster functional recovery, minimal complications, and a shorter length of stay. It can also improve patient care quality and reduce opioid exposure and dependence. ERACS aims to provide a comfortable patient experience by accelerating the process of patient care and recovery by prioritizing patient safety. However, the obstacle is consistency in carrying out the ERACS protocol in each related service unit, such as polyclinic, operating rooms, and treatment rooms, to implement each protocol comprehensively and optimally.